Perceived Service Quality and Overall Satisfaction: From a Segmentation Perspective Unique to Golf Spectators - Tomo Tokuyama; Chris Greenwell; Junko Deguchi; Masashi Shinjo (Journal of Applied Sports Management, 2023)
The purpose of the current study is to examine differences in the relationships between specific aspects of the service encounter and customer satisfaction attributable to consumers’ viewing situation and frequency of attendance. Questionnaires were distributed to spectators attending a major women’s golf tournament in Japan, and study participants were asked to rate various service elements and their level of attendance satisfaction. Respondents were grouped by viewing situations (one location, following a specific pairing, or moving the course randomly) and past attendance frequency (new spectators, light spectators, or frequent spectators). Shuttle bus service predicted satisfaction regardless of segment. Merchandise predicted satisfaction for consumers staying in one spot, informational signage predicted satisfaction for followers, and tournament staff predicted satisfaction for movers. Informational signage was correlated with satisfaction for both light and frequent attendees, and tournament staff predicted satisfaction for frequent attendees. Tournament organizers can adjust service strategies to maximize satisfaction for different spectator segments.
Keywords: Golf spectators; service elements; attendance satisfaction; viewing situation